Assessing the Impact of Perda No 1 Year 2024 on PBB-P2 Taxpayer Compliance: Evidence on Tax Knowledge, Socialization, Tax Sanctions, and Policy Adjustment - Syahru Siamunnisa; Dev Anand (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Taxpayer compliance has become a critical issue in the context of regional tax reform following the enactment of Local Regulation No. 1 of 2024 in Cirebon City, particularly in relation to behavioral determinants of local property taxation (PBB-P2) This study aims to analyze the effects of tax knowledge, tax socialization, tax sanctions, and policy adjustment on individual taxpayer compliance. A quantitative approach was employed using a survey method, with data collected from 400 individual taxpayers registered at KPP Pratama Cirebon through purposive sampling. Questionnaires were distributed both offline and online. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS version 4.1.1.7, including evaluation of the measurement model (outer model) and structural model (inner model) to assess validity, reliability, and hypothesized relationships. The findings reveal that tax knowledge, tax socialization, tax sanctions, and policy adjustment positively and significantly influence taxpayer compliance. Tax knowledge enhances understanding of rights and obligations, socialization strengthens awareness of tax responsibilities, sanctions reinforce compliance through deterrent effects, and adaptive policy adjustments provide greater certainty and convenience. These results highlight the importance of integrated educational, regulatory, and policy strategies to improve local tax compliance